Security by Design for Industrial Control Systems from a Cyber–Physical System Perspective: A Systematic Mapping Study - Ahmed Elmarkez; Soraya Mesli-Kesraoui; Pascal Berruet; Flavio Oquendo (Machines)
Industrial Control Systems (ICSs), a specialized type of Cyber–Physical System, have shifted from isolated and obscured environments to ones exposed to diverse Information Technology (IT) security threats, which are now highly interconnected. Their adoption of IT introduces vulnerabilities which they were not originally designed to handle, posing critical risks. Thus, it’s imperative to integrate security measures early in CPS development, particularly during the design and implementation phases, to mitigate these vulnerabilities effectively. This study aims to identify, classify, and analyze existing research on the security-by-design paradigm for CPSs, exploring trends and defining the characteristics, advantages, limitations, and open issues of current methodologies. A systematic mapping study was conducted, selecting 55 primary studies through a rigorous protocol. The findings indicate that the majority of methodologies concentrate on the design phase, frequently overlooking other stages of development. Moreover, while there is a notable emphasis on security analysis across most primary studies, there is a notable gap in considering the integration of mitigation measures. This oversight raises concerns about the efficacy of security measures in real-world deployment scenarios. Additionally, there is a significant reliance on human intervention, highlighting the need for further development in automated security solutions. Conflicts between security requirements and other system needs are also inadequately addressed, potentially compromising overall system effectiveness. This work provides a comprehensive overview of CPS security-by-design methodologies and identifies several open issues that require further investigation, emphasizing the need for a holistic approach that includes vulnerability handling, clear security objectives, and effective conflict management, along with improved standard integration, advanced validation methods, and automated tools.